Struktur Biaya dan Penerimaan Usahatani Nanas Madu (Ananas sativus) di Kecamatan Basarang Kabupaten Kapuas - Noorlatifah Noorlatifah; Hamdani Hamdani (Universitas Lambung Mangkurat, 2012)
The purposes of this study are to determine the costs, revenue, net income and feasibility of honey pineapple farming in the Kecamatan Basarang, Kabupaten Kapuas, Central Kalimantan. Proportionate random sampling was used to determine the sample, which 15% of population was taken. The results showed that the average cost was Rp. 33,958,066 per hectare including the land rent, or Rp 24,958,066 without land rent. The average revenue was Rp. 102,000,000 per hectare. Furthermore, the average profit / net income obtained was Rp. 68,041,934 per hectare for 28 months (2 years and four months). The feasibility criteria were determined by using investment criteria, that were: NPV, BCR and profit rate. The NPV, BCR and profit rate was Rp 53,658,538; 2.8; and 200%, respectively. Thus, the overall indicators indicated that honey pineapple farming was financially feasible. The increasing in production cost and the decreasing in benefit were not change the feasibility rate.